Human papillomavirus DNA detection, p16INK4a, and oral cavity cancer in a U.S. population. (April 2019) - Hernandez, Brenda Y.; Lynch, Charles F.; Chan, Owen T.M.; Goodman, Marc T.; Unger, Elizabeth R.; Steinau, Martin; Thompson, Trevor D.; Gillison, Maura; Lyu, Christopher; Saraiya, Mona
Graphical abstract: Strong expression of p16 in a gingival tumor positive for HPV 18 is depicted. Of the 122 oral cavity cancer cases, joint positivity for HPV 16/18 and p16 INK4a was observed in 33% (4/12) of gingival tumors compared to 0% (0/6)–8% (2/26) for other subsites (p = 0.01). Highlights: HPV DNA and p16 INK4a were each detected in ∼30% of oral cavity cases but were poorly correlated. HPV 16, found in 22% of tumors, was the most frequently detected of seven genotypes. Joint positivity for HPV 16 and/or 18 and p16INK4a was observed in 7% of cases. HPV 16/18 and p16 INK4a positivity was highest in gingival tumors (33%) and in more recently diagnosed cases. Neither HPV DNA nor p16INK4a were associated with overall survival. Abstract: Objectives: The role of HPV in oral cavity cancers was investigated using two markers of viral exposure. Materials and methods: HPV DNA and p16 INK4a expression were evaluated in tumor tissue from a U.S. population-based sample of 122 invasive oral cavity cancer cases. Results: HPV DNA was detected in 38 of 122 (31%) oral cavity tumors. Seven genotypes were detected including HPV 16, which was found in 22% of tumors. p16 INK4a was expressed in 30% of tumors and was poorly correlated with HPV DNA detection (Kappa <0.1). Joint positivity for HPV 16 and/or 18 and p16 INK4a was observed in only 7% of cases. When comparing cases diagnosed in 1993–1999 and in 2000–2004, positivity for HPV DNA 16/18 increased from 19% to 39% (p = 0.02) and joint HPV 16/18 – p16 INK4a positivity increased from 0% to 12% (p = 0.01). For gingival tumors, HPV 16 and/or 18 positivity was 67% compared to 11–38% for other sites (p = 0.02); joint HPV 16/18 – p16 INK4a positivity was 33% compared to 0–8% for other sites (p = 0.01). The association of HPV with gingival tumors and more recent diagnosis period remained after adjustment for age and stage (p < 0.05). Neither HPV DNA nor p16 INK4a were associated with overall survival. Conclusions: Based on both HPV DNA and p16 INK4a, HPV is etiologically linked to a limited subset of oral cavity cancers. However, the role of HPV in oral cavity cancer may vary widely by subsite and may have increased over time, similar to trends observed for oropharyngeal cancer.